ENINGKATAN HASIL BELAJAR TEKS PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI SMP - ., Haryatmo (Universitas Tanjungpura, 2021)
This research started from the researcher's reflection on the low learning achievement of students in Class IXA on the procedural text material. The researchers conducted classroom action research (CAR) using the Discovery Learning Model on the procedural text material. The data collection technique used a test in the form of written test. The data collection instrument used aquestion sheet that had been prepared by the researcher as well as the teacher at the end of each lesson. The data analysis used in this study used an interactive model of qualitative data analysis (Miles & Huberman), which includes: data reduction, data presentation and conclusion drawing.These three components flow continuously and interact with each other, so it is known as interactive model analysis. The results of the study indicated that learning with the Discovery Learning model can be used to improve students’ learning achievement in procedural text material. Based on the table of students’ learning achievement in cycles I and II, it appears that in general better. In the first cycle with an average value of 69.25 to 75.89 in the second cycle, or an increase of 9.59%. While the number of students who achieved completeness in the first cycle was 18, and in the second cycle as many as 26. Based on the results of the study, it can be concluded that learning with the discovery learning model used in this study is able to improve students’ learning achievement in procedural text material for class IX A students at SMP Negeri 4 Ketapang.